PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT BERBANTUAN QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJARN SISWA PADA MATERI BILANGAN BERPANGKAT DI KELAS VIII SMP NEGERI 21 PALU - Erma Nurhijjah Rakasiwi; Fajriani Fajriani; Baharuddin Paloloang; Ibnu Hadjar (Universitas Tadulako, 2025)
This study aims to describe the application of the Team Games Tournament type cooperative learning model assisted by quizizz in improving student learning outcomes on the material of rank numbers in class VIII SMP Negeri 21 Palu. The subjects in this study were all students of class VIII SMP Negeri 21 Palu. The research instruments used consisted of observation sheets, test questions and interviews. The results showed that the Team Games Tournament type cooperative learning model assisted by quizizz could improve student learning outcomes on the material of power numbers in class VIII SMP Negeri 21 Palu, by following the steps of the Team Games Tournament type cooperative learning model, namely: (1) class presentation, (2) learning in groups, (3) games, (4) tournament, and (5) team recognition. The results of the end-of-action test showed that in cycle I it was seen that students were still difficult in solving the problems given so that there were some students who could not solve the problem and there were students who still had difficulty in determining negative power numbers. Whereas in cycle II students had a better understanding of how to work on power numbers in determining the properties of power numbers. Based on the percentage of Classical Learning Completeness (KBK) in cycle I, it shows that students have difficulty in solving negative power number problems. This can be seen from the number of students who completed, namely out of 22 students who took the final test, there were only 14 students who got a complete score or got a score that reached the KKM of 75, so the percentage in cycle I only reached 63.63%. Whereas in cycle II shows that of the 17 students who took the final test, 16 students obtained a complete score or reached the KKM which is 75, so the percentage results in cycle II reached 93.11%. In addition, the results of observations of teacher activities in managing learning and student activities in participating in learning show an increase in each cycle. Based on the data from the research results, it can be concluded that the cooperative learning model of Team Games Tournament type assisted by quizizz can improve student learning outcomes on rank number material in class VIII SMP Negeri 21 Palu.